Are Patients Sufficiently Informed about Contact Lens Wear and Care?. Issue 12 (26th December 2022) - Alonso, Silvia; Yela, Sandra; Cardona, Genis
Abstract : SIGNIFICANCE: Frequent and effective patient-practitioner communication is essential to ensure that instructions regarding contact lens use, care, and maintenance are understood and followed. Given the relevance of good patient compliance, the responsibility of practitioners to provide adequate information may not be neglected. PURPOSE: This study aimed to determine the content and type of information licensed optometrists in Spain provide their patients during the first contact lens fitting and at follow-up visits. METHODS: A self-reported ad hoc survey was distributed to licensed optometrists in Spain to investigate, among other factors, whether practitioners provided information on several aspects of contact lens use and maintenance, how was this information provided, and whether in-office practical demonstrations were conducted at all contact lens appointments. RESULTS: Respondents of 321 surveys had a median of 20 years of contact lens fitting experience and worked on independent practices (67.6%), and national (29.0%) and regional chains (3.4%). Type of practice influenced continuous education habits ( P = .03). Overall, 28.0% of participants did not always instruct patients on the need to rub contact lenses, 34.3% did not always address contact lens replacement, and 6.8% did not always explain storage case hygiene and replacement. At the follow-up visit, only 8.4% of respondents asked their patients to demonstrate their care routines. Information was mostly oral (48.6%) or oral and written (43.0%). Contact lens–related complications were reported more frequently by participants with less continuous education training ( P = .01), by those not always recommending rubbing ( P = .002), and by those not providing written information about storage case hygiene and replacement ( P = .002). CONCLUSIONS: Patient-practitioner communication was good, albeit several areas were identified where information was insufficient or not provided in a correct and timely format. Precise, written information on rubbing and storage case hygiene and replacement may improve compliance and assist in avoiding complications and dropout.